2012
DOI: 10.1176/appi.ajp.2010.10040555
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Behavioral Treatment of Body Image Disturbance in a Congenitally Blind Patient With Anorexia Nervosa

Abstract: C lin ic a l C a s e C o n fe r e n c e 1 6 a jp.p sych ia tryo n lin e.o rg A m J Psych ia try 1 6 9 :1 , Ja nu a ry 2 0 1 2A m J Psych ia try 1 6 9 :1 , Ja nu a ry 2 0 1 2 a jp.p sych ia tryo n lin e.o rg A m J Psych ia try 1 6 9 :1 , Ja nu a ry 2 0 1 2 a jp.p sych ia tryo n lin e.o rg

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
1
5
0
2
Order By: Relevance
“…She also compared her body to those of other women by touching parts of their bodies during handshaking or by using auditory cues (e.g., the tone, volume and pitch of their voices) to estimate their body sizes. Interestingly, this auditory recognition of material properties was also recently reported in a single case of anorexia nervosa in a blind patient 22 and earlier in a study of blind children. 23 B. avoided social meals because she was concerned that her fellow diners would be judging her physique and disability negatively “just look at this fat blind girl eating…”.…”
Section: Case Reportsupporting
confidence: 78%
See 1 more Smart Citation
“…She also compared her body to those of other women by touching parts of their bodies during handshaking or by using auditory cues (e.g., the tone, volume and pitch of their voices) to estimate their body sizes. Interestingly, this auditory recognition of material properties was also recently reported in a single case of anorexia nervosa in a blind patient 22 and earlier in a study of blind children. 23 B. avoided social meals because she was concerned that her fellow diners would be judging her physique and disability negatively “just look at this fat blind girl eating…”.…”
Section: Case Reportsupporting
confidence: 78%
“…Although anorexia nervosa and bulimia nervosa are generally thought to be exceptional in the visually impaired, 13 case reports of eating disorders in this population 14–22 suggest that the inability to see does not protect against the development of an eating disorder. 10, 15 Yet, the roles of appearance investment and thin‐ideal internalization as possible risk factors for eating disorders in the blind have been generally neglected.…”
Section: Introductionmentioning
confidence: 96%
“…No que se refere às implicações da cegueira congênita em diferentes aspectos da imagem corporal, os resultados apontam incongruência teórica. Pode-se perceber que grande parte dos estudos (40%) aponta que características específicas da cegueira congênita são importantes precursoras de alterações negativas da imagem corporal (Fernández-Aranda, Crespo, Jiménez-Murcia, Krug, & Vallejo-Ruiloba, 2006;Kinsbourne, & Lempert, 1980;Lev-Wiesel, Aharoni, & Bar-David, 2002;Sharp, 1993;Shulman, 1986;Touyz, O'Sullivan, Gertler, & Beumont, 1988;Vandereycken, 1986;Yager, Hatton, & Ma, 1986); 25% apontam que essas características implicam positivamente no desenvolvimento saudável da imagem corporal (Ashikali & Dittmar, 2010;Baker, Sivyer, & Towell, 1998;Ma & Han, 2011;Pierce & Wardle, 1996;Resnick, 1983); 10% indicam que alterações da imagem corporal em pessoas com cegueira congênita devem ser avaliadas a partir de um complexo conjunto de fatores, que incluem tanto características específicas da cegueira congênita quanto preocupações com a forma e dimensão corporal (Ostojic & Hansen ,2013;Thomas, Weigel, Lawton, Levendusky, & Becker, 2012); e 25% não fizeram menção direta a respeito das implicações da cegueira na imagem corporal (Bullington & Karlsson, 1997;Kaplan-Myrth, 2000;McFarlane, 1989;Morgado & Ferreira, 2010;Morgado, Ferreira, Campana, Rigby, & Tavares, 2013).…”
Section: Resultsunclassified
“…Mais recentemente, alguns estudos têm enfatizado a necessidade de considerar um conjunto de fatores no desenvolvimento e manutenção dos transtornos alimentares em pessoas que não enxergam desde idades precoces, que englobam tanto características peculiares do desenvolvimento, quanto alterações relacionadas à imagem corporal. Thomas et al (2012) encontraram que características peculiares da cegueira (suposições sobre a própria aparência física e a do outro e ausência de feedback visual corretivo), assim como preocupações com a imagem corporal (checagem e evitação), são centrais no quadro do transtorno alimentar. De igual modo, Ostojic e Hansen (2013) afirmaram que além de características peculiares da cegueira (inabilidade de ver o corpo do outro e de olhar no espelho para obter referências do próprio corpo), é necessário também considerar o papel de pressões socioculturais percebidas e internalização do ideal de magreza nos casos de transtorno alimentar em pessoas com cegueira congênita.…”
Section: Transtorno Alimentarunclassified
“…Women living with VI were initially believed to be protected from developing an eating disorder due to reduced visual exposure to cultural standards of attractiveness in the media and a limited capacity to check their appearance in mirrors and visually represent the body (Baker et al, 1998). However, case studies of women living with VI diagnosed with an eating disorder have revealed that body image disturbances can both contribute to and perpetuate the disorder (Bemporad, Hoffman, & Herzog, 1989; Dunn & Coorey, 1982; Fernández-Aranda, Crespo, Jiménez-Murcia, Krug, & Vallejo-Ruiloba, 2006; McFarlane, 1989; Sharp, 1993; Simeunovic-Ostojic & Hansen, 2013; Thomas, Weigel, Lawton, Levendusky, & Becker, 2012; Touyz, O’Sullivan, Gertler, & Beumont, 1988; Vandereycken, 1986; Yager, Hatton, & Ma, 1986). Some studies did not indicate body image disturbance as a perpetuating factor, but rather highlighted the importance of other life stressors such as developmental problems (McFarlane, 1989), susceptibility to misperceiving body size and weight (Thomas et al, 2012; Vandereycken, 1986), maladaptive stress-coping mechanisms (Fernández-Aranda et al, 2006), and issues of autonomy, independence, mobility, and plans for the future (Touyz et al, 1988).…”
Section: Women Living With Vision Impairmentmentioning
confidence: 99%